1996
DOI: 10.1021/jm9507082
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of the Quinolone Antibacterials against Mycobacteria:  Effect of Structural Changes at N-1 and C-7

Abstract: The re-emergence of tuberculosis infections which are resistant to conventional drug therapy has demonstrated the need for alternative chemotherapy against Mycobacterium tuberculosis. As part of a study to optimize the quinolone antibacterials against M. tuberculosis, we have prepared a series of N-1- and C-7-substituted quinolones to examine specific structure-activity relationships between modifications of the quinolone at these two positions and activity against mycobacteria. The compounds, synthesized by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 36 publications
7
54
1
5
Order By: Relevance
“…Analysis of the quinolone structureactivity relationship showed that these seven compounds shared certain structural features (C-8 with or lacking a substitution, N-1 cyclopropyl group, a ring at C-7, and a fluorine at C-6) (see Table 1). Quinolone structure-activity relationship analyses done to date for quinolones and mycobacteria (21,24,32,38) were not based on target inhibition, as in our study, but on MICs, which are the result of target inhibition and many other factors of activity, such as cell wall permeability and efflux (19). Moreover, these analyses were done with nontuberculous mycobacteria (M. smegmatis, M. avium, and M. fortuitum) and not with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 79%
“…Analysis of the quinolone structureactivity relationship showed that these seven compounds shared certain structural features (C-8 with or lacking a substitution, N-1 cyclopropyl group, a ring at C-7, and a fluorine at C-6) (see Table 1). Quinolone structure-activity relationship analyses done to date for quinolones and mycobacteria (21,24,32,38) were not based on target inhibition, as in our study, but on MICs, which are the result of target inhibition and many other factors of activity, such as cell wall permeability and efflux (19). Moreover, these analyses were done with nontuberculous mycobacteria (M. smegmatis, M. avium, and M. fortuitum) and not with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 79%
“…The effective antimycobacterial activity of sparfloxacin has been reported previously by other investigators (1,14), yet our results showed that this drug was not particularly active against the resistant isolates that harbored gyrA mutations. For moxifloxacin, gatifloxacin, and sitafloxacin, their superior activities have been attributed to the special structure-activity relationship of the C-8-methoxy and C-8-halogen substitution in the chemical structure of the prototype fluoroquinolones (3,13,16,17,24,34). These new members with this substitutions can have stronger bacteriostatic and lethal activities against M. tuberculosis, as shown by their lower MICs even among the gyrA mutants (7,8,12,20,25,30).…”
Section: Discussionmentioning
confidence: 99%
“…Nowe generacje fluorochinolonów zostały umieszczone w zaleceniach, a ich skuteczność w leczeniu MDR-TB wynika z faktu, iż ta grupa leków cechuje się większą penetracją do wnętrza makrofagów niż ofloksacyna czy cyprofloksacyna [64,65]. Określając wartość MIC dostępnych fluorochinolonów w stosunku do prątka gruź-licy, wykazano duże zróżnicowanie zależne od obecności grupy metoksylowej w pozycji C8 [66,67]. Zwrócono jednak uwagę na fakt, że fluorochinolony ze znaczną aktywnością przeciwbakteryjną ujawniały zbyt dużo działań ubocznych, niekiedy toksycznych, np.…”
Section: Fluorochinolony W Leczeniu Gruźlicyunclassified